Simultaneous determination of phenylalanine and tyrosine levels in human blood obtained by the dried spot technique for monitoring of patients with phenylketonuria - Kopčil, Michal; Kanďár, Roman (Journal of pharmaceutical and biomedical analysis, 2025)
Monitoring patients with phenylketonuria (PKU) requires accurately measuring phenylalanine and tyrosine levels in a small volume of blood samples obtained by the dried blood spot (DBS) technique. The aim was to study selected parameters influencing the quantitative results. Phenylalanine and tyrosine were extracted from DBS samples with methanol, and 5 internal standard introduction techniques were tested. Phenylalanine and tyrosine levels were measured in 6-mm discs punched from DBS, pre-punched 9-mm discs containing the entire DBS sample, and liquid blood by HPLC-MS-MS. Levels in 6-mm discs punched from DBS measured by HPLC-MS/MS were compared with those measured by the HPLC-FLD. The analytical parameters of the method are satisfactory, linearity in the range of 25-1200 μmol/L (LOD, LOQ and LLOQ values 0.2 μmol/L, 0.5 μmol/L and 3.8 μmol/L for phenylalanine, 0.5 μmol/L, 1.5 μmol/L and 5.1 μmol/L for tyrosine), within-run precision 1.8 %-3.7 % for phenylalanine, 1.9 %-2.7 % for tyrosine, between-run precision 4.7 %-5.9 % for phenylalanine, 4.1 %-5.4 % for tyrosine, recovery 93.8 %-100.4 % for phenylalanine and 93.7 %-99.1 % for tyrosine. Good agreement was found between phenylalanine and tyrosine concentrations in 6-mm discs punched from DBS (R = 0.896, p < 0.001, and R = 0.907, p < 0.001, respectively), pre-punched 9-mm discs containing the entire DBS sample (R = 0.960, p < 0.001, and R = 0.950, p < 0.001, respectively) and liquid blood, as well as between phenylalanine and tyrosine concentrations obtained by HPLC-MS/MS and HPLC-FLD (R = 0.968, p < 0.001, and R = 0.984, p < 0.001, respectively). The presented method is suitable for monitoring patients with PKU.
Keywords: fenylketonurie; Dried blood spot; Dried Blood Spot Testing; Liquid chromatography with mass spectrometry and fluorescence detection; Phenylalanine; Tandem Mass Spectrometry; test suché kapky krve; Reproducibility of Results; vysokoúčinná kapalinová chromatografie; Tyrosine; lidé; Phenylketonurias; Parameters affecting quantitative results; reprodukovatelnost výsledků; limita detekce; Chromatography, High Pressure Liquid; fenylalanin; tandemová hmotnostní spektrometrie; tyrosin; Limit of Detection; Humans